2017
DOI: 10.5664/jcsm.6728
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Characteristics and Temperament in Preterm Children at Two Years of Age

Abstract: Preterm children showed sleep pattern problems and disturbance, predominance of attention problems, and negative emotionality related to sleep disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 59 publications
1
39
1
Order By: Relevance
“…However, they did not find more nocturnal awakenings or shorter sleep duration compared with their control group, nor did they find that total sleep time or nocturnal awakenings were associated with SDQ total-scores. Caravale et al studied 2-year-old preterm children (mean GA 31 weeks), and found that they had more frequent sleep difficulties during the night, and that these difficulties were related to problems with emotions and attention,26 which is in agreement with our findings. It is worth noting that Perkinson-Gloor et al excluded children with severe developmental delay25 and that Caravale et al included only children with normal cognitive, language, and motor development26 as opposed to no selections in our study.…”
Section: Discussionsupporting
confidence: 92%
“…However, they did not find more nocturnal awakenings or shorter sleep duration compared with their control group, nor did they find that total sleep time or nocturnal awakenings were associated with SDQ total-scores. Caravale et al studied 2-year-old preterm children (mean GA 31 weeks), and found that they had more frequent sleep difficulties during the night, and that these difficulties were related to problems with emotions and attention,26 which is in agreement with our findings. It is worth noting that Perkinson-Gloor et al excluded children with severe developmental delay25 and that Caravale et al included only children with normal cognitive, language, and motor development26 as opposed to no selections in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In a separate study, prematurely born children (31.1 ± 2.4 weeks GA, 1600.8 ± 501.2 g, mean±SD) studied at 2 years of age were shown to get to sleep more quickly and were earlier to rise, but had increased incidences of night waking and restlessness and breathing problems associated with poor attention, greater negative emotions, and hyperactivity (Caravale et al . ). In a similar cohort of children, a reduction in sleep duration and quality of sleep was associated with an increased risk of attention deficit hyperactivity disorder (Gossel‐Symank et al .…”
Section: Introductionmentioning
confidence: 97%
“…Infant sleep quality and development can be modulated by a number of biopsychosocial factors [23]. These factors include inherited child's characteristics, such as temperament [24] or chronotype [19], perinatal characteristics such as season of birth [25] or photoperiod [26], and environmental characteristics such as parental stress [27]. Following this line of research, our recent study reported that some maternal risk factors during pregnancy are related to infants' sleep difficulties at three months of age [28].…”
Section: Introductionmentioning
confidence: 97%